The position of the local administration (municipalities) on tax reform projects in Algeria 1845 – 1930 - Hamel, Abdelmonaeme; BENMEBROK, Neoui (Journal of Human Sciences, 2020)
The French occupation authorities resorted to imposing various taxes on the Algerian society which led to its impoverishment. The tax revenues were in the interest of the settlers only. The tax system is characterized by double taxation. Taxation led to serious economic and social imbalances.